The Relationship of Learning Entrepreneurship, Enterprise Motivation, And the Family Environment with Enterprise Interest in Students - Rochanawati, Ida; Efi, Agusti (LPPM Undiksha, 2020)
Many of Bunda's Tourism Diploma graduates are still unemployed because some are less interested in becoming self-employed. It because students are not motivated to become entrepreneurs, and the family environment is not yet supported. This study aimed to measure: the relationship between entrepreneurial learning outcomes, entrepreneurial motivation, and family environment with interest in entrepreneurship. This type of research is descriptive correlational. This research population is all students of the Hospitality study program of the Bunda Padang Tourism Academy, batch 2017 and 2018, totaling 61 students. The sample in this study were 61 students using the total sampling technique. The data collection instrument used a questionnaire using a Likert scale and data analysis methods, including simple correlation and multiple correlations. Research is expected to increase students' entrepreneurial knowledge through attitudes, knowledge, and skills to overcome entrepreneurial tasks' complexity, providing real experiences for students to carry out entrepreneurial practices.